Pentingnya Menuntut Ilmu: Perspektif Islam dan Dampaknya pada Karakter Pembentukan Individu - Arrumaisha Fasya Nuriy; Deshi Karunia Hajarwati; Desra Reifka Rhaudia; Elisya Laesya Tasya; Erna Widyastuti; Rizki Amrillah (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2024)
Education in Islam is not only about acquiring knowledge, but also forming good character and developing noble morals. Demanding knowledge is considered a practice in worship that will be rewarded by Allah Swt. In the Quran, Allah Swt repeatedly emphasizes the importance of seeking knowledge and gaining a deep understanding of religion. The research method used is a qualitative method with a literature study approach. Data were obtained from various literature sources such as books, journals, articles, and other documents relevant to the research topic. The results and discussion show that character education has a significant impact on the formation of individuals, helping them develop positive self-attitudes and qualities. The conclusion of this research is that studying in an Islamic perspective is a form of worship that needs to be done intensely and with dedication. By maintaining ethics and developing good morals, the knowledge gained will be useful and bring blessings in shaping individual character.